Corrigendum to “Adulteration in paneer (Indian cottage cheese): A review of practices, detection, and public health implications – a critical analysis”[Food Control 187 (2026) 112163] - A. Surendra Babu; P. Sankarganesh; V. Parthasarathy; K. Rajkumar; Meenatai Gunderao Kamble (Food Control, 2026)

Retraction notice to “Systematic green synthesis of silver oxide nanoparticles for antimicrobial activity” [Environ. Res. 202 (2021) 111627] - M. Mani; R. Harikrishnan; P. Purushothaman; S. Pavithra; P. Rajkumar; S. Kumaresan; Dunia A. Al Farraj; Mohamed Soliman Elshikh; Balamuralikrishnan Balasubramanian; K. Kaviyarasu (Environmental Research, 2026)

Adulteration in paneer (Indian cottage cheese): A review of practices, detection, and public health implications – a critical analysis - A. Surendra Babu; P. Sankarganesh; V. Parthasarathy; K. Rajkumar; Meenatai Gunderao Kamble (Food Control, 2026)

Exploring wild rices for photosynthetic efficiency improvement in rice - Kanchan Jumrani; Dipti Ranjan Pani; Mridul Chakraborti; Mirza Jaynul Baig; Viswanathan Chinnusamy; Palanisamy Veeraya; Ritu Tiwari; Dhammaprakash P. Wankhede; Rajkumar Subramani; Kanakasabapathi Pradheep; Parimalan Rangan (Physiology and Molecular Biology of Plants, 2026)
Photosynthesis is a key determinant for plant productivity, understanding its genetic basis will aid its improvement. The photosynthesis trait is primarily measured in terms of carbon and light utilization, using gas exchange and chlorophyll fluorescence methods. We report in this study, the extent of variability for photosynthetic trait in wild rice relatives, comprising a total of 26 taxa (22 wild species), using an infrared gas analyzer. The scale of measures used were, PN (net photosynthetic rate), E (transpiration), gs (stomatal conductance), Ci (intercellular CO 2 ), Ci/Ca (ratio of intercellular to ambient CO 2 ), WUE (water use efficiency), CE (carboxylation efficiency), Fv′/Fm′ (ratio of variable to maximum fluorescence, photosynthesis efficiency), qP (photochemical quenching), qN (non-photochemical quenching), ΦPSII (quantum yield of photosystemII), and ETR (electron transport rate). These were subjected to variability (ANOVA and PCA) and association (correlation matrices and path analysis) studies. The maximum PN was observed in Oryza australiensis , followed by Oryza officinalis and Oryza barthii . Maximum qP was observed in Oryza latifolia which was at par with O . australiensis , and Oryza alta . Highest CE was observed in O . australiensis . The CE values for O . barthii , Oryza grandiglumis and O. latifolia were at par with O . australiensis . Transcriptomic analysis for flag leaf between APO, the high efficient photosynthetic genotype with indica rice cultivar BAM4234 revealed key candidate genes underlying photosynthesis traits. These findings underscore the value of wild species and their alleles in expanding the photosynthetic capacity of rice potentially using classical breeding approaches.

Effects of an intervention for a liquefied petroleum gas cook-stove with free fuel on food insecurity and dietary diversity among women and infants: a multi-country randomized controlled trial - Sheela S. Sinharoy; Rina Das; Anaité Diaz-Artiga; Lisa M. Thompson; Ghislaine Rosa; John McCracken; Miles A. Kirby; Carla Tarazona-Meza; Vigneswari Aravindalochanan; Shirin Jabbarzadeh; Jiantong Wang; Ajay Pillarisetti; et al. (Food Security, 2026)

Molecular delineation, development and validation of functional markers for brachytic2 (br2) gene governing dwarfing plant height in maize - Govinda Rai Sarma; Rashmi Chhabra; Vignesh Muthusamy; Shanmugavadivel P. Subramaniam; Gaurav Sharma; Hriipulou Duo; Vinay Rojaria; Rajkumar U. Zunjare; Viswanathan Chinnusamy; Firoz Hossain (Physiology and Molecular Biology of Plants, 2025)

Amino acid composition of pigeon pea varieties through HPTLC - Kirankumar P. Suthar; Diwakar Singh; Nitin B. Patel; Digvijay A. Chauhan; Rajkumar B. Katagi; Komal G. Lakhani (Vegetos, 2025)

MOF derived ZnO nanostructures modified with CoW12-polyoxometalates for enhanced sunlight driven degradation of methylene blue, ofloxacin and their mixtures - Nitin A. Tupsamindar; Arun S. Chopade; Sagar A. Chaudhari; Abhijit N. Kadam; Sandip R. Sabale; Vaishali Patil; Mohaseen S. Tamboli; Raisuddin Ali; Nguyen Tam Nguyen Truong; Vashishtha M. Gurame; Dattakumar S. Mhamane; Vijaykumar P. Ubale; et al. (Journal of Water Process Engineering, 2025)

Household air pollution and blood pressure among adult women participants of the Household Air Pollution Intervention Network Trial: An exposure-response analysis - Ajay Pillarisetti; Wenlu Ye; Jennifer L. Peel; Howard Chang; Lindsay J. Underhill; Kalpana Balakrishnan; Anaité Díaz-Artiga; John P. McCracken; Ghislaine Rosa; Lisa M. Thompson; Vigneswari Aravindalochanan; Dana Boyd Barr; et al. (Environmental Research, 2025)

Gestational and postnatal exposures to fine particulate matter (PM2.5) and their association with acute ear infections, diarrhea, respiratory symptoms, and mortality: A longitudinal study of infants in the multicountry Household Air Pollution Intervention Network (HAPIN) trial - Brandie Banner Shackelford; Kyle Steenland; Miles A. Kirby; Kalpana Balakrishnan; Marilú Chiang; Anaité Diaz-Artiga; John P. McCracken; Lisa M. Thompson; Ghislaine Rosa; Lance A. Waller; Shirin Jabbarzadeh; Jiantong Wang; et al. (Environmental Research, 2025)

Enhanced dual removal of chromium and lead ions from water using biopolymer modified ferric–alumina layered double hydroxides - V. Nithya Priya; D. Karthigaimuthu; S.Sasi Florence; M. Rajkumar; S.P.Linto Sibi; M.S. Sobana; J. Mobika; V. Vijayalakshmi; P. Ahila (Journal of Environmental Chemical Engineering, 2025)

Behaviour of prestressed hollow core slabs after exposure to elevated temperatures: an experimental and numerical approach - T M Jeyashree; P R Kannan Rajkumar (Innovative Infrastructure Solutions, 2025)

Association of Lasiodiplodia theobromae and L. iraniensis with spindle rot of coconut, Cocos nucifera L. as revealed through polyphasic approach - V.H. Prathibha; M.K. Rajesh; Daliyamol; Rajkumar; J. Keerthana; K.P. Thejasri; B.J. Nirmal Kumar; K.R. Latha; P. Subramanian; Vinayaka Hegde (Physiological and Molecular Plant Pathology, 2025)

Resistance mechanism of energy canes developed from Saccharum spontaenum and Erianthus arundinaceus against sugarcane borer pests - M. Punithavalli; P. Govindaraj; M. Balaji Rajkumar (Journal of Asia-Pacific Entomology, 2025)

UTF1 Expression is Important for the Generation and Maintenance of Human iPSCs - Khyati Raina; Kirti Modak; Chitra Premkumar; Gaurav Joshi; Dhavapriya Palani; Krittika Nandy; Yazhini Sivamani; Shaji R. Velayudhan; Rajkumar P. Thummer (Stem Cell Reviews and Reports, 2025)

First record of fruit rot in soursop caused by Lasiodiplodia theobromae in India - Prathibha V. H.; Panjavarnam G.; Daliyamol; Rajkumar; Keerthana S.; Thejasri K. P.; Gangaraj K. P.; Rajesh M. K.; Vinayaka Hegde (Journal of Plant Pathology, 2025)

Rice Transcriptomics Reveal the Genetic Determinants of An In Planta Photorespiratory Bypass: a Novel Way to Increase Biomass in C3 Plants - Parimalan Rangan; Dhammaprakash P. Wankhede; Rajkumar Subramani; Viswanathan Chinnusamy; Pooja Pathania; Arti Bartwal; Surendra K. Malik; Mirza Jaynul Baig; Anil Rai; Kuldeep Singh (Plant Molecular Biology Reporter, 2025)

Allometric scaling and carbon sequestration in agroforestry species of the Western Himalayas: a model-based approach - Megha VR; R. Kaushal; Sadikul Islam; Uday Mandal; Harsh Mehta; Rajkumar; J. M. S. Tomar; Anand Kumar Gupta; Anupam Barh; Vishwal Madhav P; Vibha Singhal; Rajiv Pandey; et al. (Environmental Monitoring and Assessment, 2025)

Sustainable selenium ions adsorption of cyclodextrin and cellulose functionalized layered double hydroxide/reduced graphene oxide nanocomposites - V. Nithya Priya; M. Rajkumar; V. Rajendran; J. Mobika; S.P. Linto Sibi; B. Veena; V. Vijayalakshmi; P. Ahila (Journal of Water Process Engineering, 2025)

Characterisation of 3D printing cake batter with xanthan gum and optimization of printing parameters using response surface methodology - Pentala Mallesham; S. Parveen; R. Pandiselvam; P. Rajkumar; Ravindra Naik (International Journal of Gastronomy and Food Science, 2024)

The qualitative and molecular categorization for genetic diversity in Withania somnifera (L.) Dunal - S. Venugopal; M. Padma; M. Rajkumar; N. Seenivasan; P. Saidaiah; G. Sathish; A.C. Jnanesha; R.S. Kumar; R.K. Lal (Ecological Genetics and Genomics, 2024)

Euwallacea perbrevis (Schedl, 1951) and associated novel fungal symbiont, Fusarium sp.: A potential cause of wilting in cocoa, Theobroma cacao in India - Shivaji Hausrao Thube; R Thava Prakasa Pandian; M. Rajkumar; Merin Babu; A. Josephrajkumar; Santhoshkumar P; B.J. Nirmal Kumar; Vinayaka Hegde; Balanagouda Patil; H. Rajashekara; T. Prabhulinga; Babasaheb B. Fand; et al. (Crop Protection, 2024)

Jamun Seed-Derived Nitrogen-Doped Carbon Dots: A Novel Microwave-Assisted Synthesis for Ultra-Bright Fluorescence and Mn7+ Detection - R. Swathi; G. Bhagavanth Reddy; Bandi Rajkumar; Dadigala Ramakrishna; P. Yadagiri Swamy (Journal of Fluorescence, 2024)

Effect of hybrid steel fibres on shear behaviour of self compacting RC beam - K. B. Ramkumar; C. Sudha; K. Gunasekaran; P. R. Kannan Rajkumar (Innovative Infrastructure Solutions, 2024)

Data processing of visible emission line coronagraph onboard ADITYA-L1 - Muthu Priyal; Jagdev Singh; B. Raghavendra Prasad; Chavali Sumana; Varun Kumar; Shalabh Mishra; S.N. Venkata; G. Sindhuja; K. Sasikumar Raja; Amit Kumar; Sanal krishnan; Bhavana S. Hegde; et al. (Advances in Space Research, 2024)

Studies on the concrete with composite cement and alccofine: from use of OPC towards low-carbon quaternary binder - B. Suresh; P. R. Kannan Rajkumar (Innovative Infrastructure Solutions, 2024)

A highly sensitive electrochemical sensor for Cr6+ ions detection using Ag NPs/rGO/quercetin modified glassy carbon electrode for water applications - G. Surendra Rajkumar; P. Senthil Kumar; Gayathri Rangasamy (Groundwater for Sustainable Development, 2024)

Effect of Pulsed Light Treatment for the Preservation of Coconut Inflorescence Sap - V. Vishnu Priya; M. Balakrishnan; R. Pandiselvam; S. Karthikeyan; P. Rajkumar; M. R. Manikantan; K. Gurusamy; P. Preetha (Sugar Tech, 2024)

Reproductive biology of green tiger shrimp Penaeus semisulcatus De Haan, 1844 in Palk Bay, southeast coast of India - M. Rajkumar; S. Lakshmi Pillai; P. Rameshkumar; R. Saravanan; S. Thirumalaiselvan; Josileen Jose; K.S. Sobhana; M. Rosalind George (Regional Studies in Marine Science, 2023)

A Review on Pyrolysis of Agro-waste and Plastic Waste into Biofuels: Shifting to Bio-based Economy - Midhun Prasad K; Murugavelh Somasundaram; B Anand; R Shankar; Rajkumar P (BioEnergy Research, 2023)

Evaluation of Effect of Tapping Frequency and Lime Coating on the Biochemical Changes and Fermentation Rate of Coconut Inflorescence Sap - V. Vishnu Priya; M. Balakrishnan; S. Karthikeyan; P. Rajkumar; M. R. Manikantan; K. Gurusamy; R. Pandiselvam (Sugar Tech, 2023)

Formation damage and improved recovery in kaolinitic high enthalpy gas fields with fabric geological settings - B. Kanimozhi; P. Rajkumar; S. Mahalingam; S. Senthil; D.S. Jayalakshmi; H. Girija Bai; Vivek Thamizhmani; Ramadoss Kesavakumar; Venkat Pranesh (Gas Science and Engineering, 2023)

Effect of packaging materials and storage temperature on the physicochemical and microbial properties of ultrasonicated mature coconut water during storage - Anjitha Jacob; I.P. Sudagar; R. Pandiselvam; P. Rajkumar; M. Rajavel (Food Control, 2023)

A Nationwide Analysis of Aneurysmal Subarachnoid Hemorrhage Mortality, Complications, and Health Economics in the USA - Lefko T. Charalambous; Syed M. Adil; Shashank Rajkumar; Robert Gramer; Elayna Kirsch; Beiyu Liu; Ali Zomorodi; Mark McClellan; Shivanand P. Lad (Translational Stroke Research, 2023)

Geological evolution of the Proterozoic Betul belt (∼2.16–0.95 Ga) of the Central Indian tectonic Zone: Its linkage to the assembly and dispersal of Columbia and Rodinia supercontinents - M. Lachhana Dora; Tushar Meshram; Srinivasa Rao Baswani; Vivek P Malviya; Dewashish Upadhyay; Mohd Shareef; Mohd Atif Raza; Sameer Ranjan; Rajkumar Meshram; Monaj Kumar Patnaik; Kirtikumar Randive (Gondwana Research, 2023)

Differential expression of m5C RNA methyltransferase genes NSUN6 and NSUN7 in Alzheimer’s disease and traumatic brain injury - Adriana PerezGrovas-Saltijeral; Anto P. Rajkumar; Helen Miranda Knight (Molecular Neurobiology, 2023)
Epigenetic processes have become increasingly relevant in understanding disease-modifying mechanisms. 5-Methylcytosine methylations of DNA (5mC) and RNA (m 5 C) have functional transcriptional and RNA translational consequences and are tightly regulated by writer, reader and eraser effector proteins. To investigate the involvement of 5mC/5hmC and m 5 C effector proteins contributing to the development of dementia neuropathology, RNA sequencing data of 31 effector proteins across four brain regions was examined in 56 aged non-affected and 51 Alzheimer’s disease (AD) individuals obtained from the Aging, Dementia and Traumatic Brain Injury Study. Gene expression profiles were compared between AD and controls, between neuropathological Braak and CERAD scores and in individuals with a history of traumatic brain injury (TBI). We found an increase in the DNA methylation writers DNMT1 , DNMT3A and DNMT3B messenger RNA (mRNA) and a decrease in the reader UHRF1 mRNA in AD samples across three brain regions whilst the DNA erasers GADD45B and AICDA showed changes in mRNA abundance within neuropathological load groupings. RNA methylation writers NSUN6 and NSUN7 showed significant expression differences with AD and, along with the reader ALYREF , differences in expression for neuropathologic ranking. A history of TBI was associated with a significant increase in the DNA readers ZBTB4 and MeCP2 ( p < 0.05) and a decrease in NSUN6 ( p < 0.001) mRNA. These findings implicate regulation of protein pathways disrupted in AD and TBI via multiple pre- and post-transcriptional mechanisms including potentially acting upon transfer RNAs, enhancer RNAs as well as nuclear-cytoplasmic shuttling and cytoplasmic translational control. The targeting of such processes provides new therapeutic avenues for neurodegenerative brain conditions. Graphical abstract

Mechanical properties and bond behaviour of steel rebar and fly ash–slag based geopolymer concrete in pull-out test - T. Srividya; P. R. Kannan Rajkumar (Innovative Infrastructure Solutions, 2023)

Characterization of the Multiple Domains of Pex30 Involved in Subcellular Localization of the Protein and Regulation of Peroxisome Number - Nayan Moni Deori; Terence Infant; Rajkumar P. Thummer; Shirisha Nagotu (Cell Biochemistry and Biophysics, 2023)

Expression of PKM2 in wound keratinocytes is coupled to angiogenesis during skin repair in vivo and in HaCaT keratinocytes in vitro - Khrystyna Sych; Simon P. Nold; Josef Pfeilschifter; Rajkumar Vutukuri; Jana Meisterknecht; Ilka Wittig; Stefan Frank; Itamar Goren (Journal of Molecular Medicine, 2023)
An injured skin is rapidly restored in a manner of wound healing. We have previously shown that intact insulin signaling and glucose uptake are fundamental to proper wound closure. Consequently, under exacerbated inflammation, compromised insulin action and glucose uptake lead to impaired healing. However, in spite of the increased attention to cell metabolism during tissue regeneration, metabolic mediators that govern cellular and physiological processes throughout skin repair remained largely elusive. Through assessment of mRNA using real-time PCR and protein blot analysis, we report that healing of cutaneous wounds comprise a boosted expression of genes involved in glycolysis, oxidative phosphorylation, pentose phosphate shunt, and glutamine anaplerosis. We further focused on the functional role of pyruvate kinase M (PKM) isoenzymes that catalyze the final and rate-limiting step of glycolysis. Whereas the expression of the metabolic constitutively active Pkm1 isozyme remained almost unchanged, Pkm2 is augmented during the inflammatory phase of healing. The immunohistochemistry and RNA in situ hybridization analysis showed a confined Pkm2 expression to keratinocytes of the hyperproliferative epithelium and, to a lesser extent, infiltrating neutrophils and monocytes as well as later on in macrophages. Notably, the expression of Pkm2 in keratinocytes facing the wound bed side colocalized with VEGF expression. The in vitro knockdown of PKM2 in HaCaT keratinocytes using small interfering (si) RNA confirmed an acute role for PKM2 in facilitating the complete induction of VEGF mRNA and protein expression in keratinocytes; this function is mainly HIF-1α independent. Key messages • Wound healing involves activation of glycolysis, oxidative phosphorylation, pentos-phosphate shunt, and replenishment of tri-carboxylic acid (TCA) cycle through glutamine anaplerosis. • The pyruvate kinase M2 (PKM2) isoform is upregulated during the inflammatory phase of cutaneous healing, mainly in keratinocytes of hyperproliferative epithelia. • In vivo, the expression of VEGF in wound keratinocytes is colocalized with PKM2. • PKM2 is required for full induction of VEGF in HaCaT keratinocytes in vitro.

Developing a numerical model to analyze the production process of PMEDM - G. Rajkumar; M. Saravanan; P. Marimuthu (Resources Policy, 2023)

A Comprehensive Review on the Role of ZSCAN4 in Embryonic Development, Stem Cells, and Cancer - Madhuri Thool; Pradeep Kumar Sundaravadivelu; S. Sudhagar; Rajkumar P. Thummer (Stem Cell Reviews and Reports, 2022)

Effect of mineral admixtures on mechanical and thermal properties of geopolymer mortar at elevated temperature - J. Baskara Sundararaj; P. R. Kannan Rajkumar; M. Sivasakthi; M. Jegan (Innovative Infrastructure Solutions, 2022)

CRISPR and iPSCs: Recent Developments and Future Perspectives in Neurodegenerative Disease Modelling, Research, and Therapeutics - Tirthankar Sen; Rajkumar P. Thummer (Neurotoxicity Research, 2022)

Evolution of an intermediate C4 photosynthesis in the non-foliar tissues of the Poaceae - Parimalan Rangan; Dhammaprakash P. Wankhede; Rajkumar Subramani; Viswanathan Chinnusamy; Surendra K. Malik; Mirza Jaynul Baig; Kuldeep Singh; Robert Henry (Photosynthesis Research, 2022)

Pex30 undergoes phosphorylation and regulates peroxisome number in Saccharomyces cerevisiae - Nayan Moni Deori; Terence Infant; Pradeep Kumar Sundaravadivelu; Rajkumar P. Thummer; Shirisha Nagotu (Molecular Genetics and Genomics, 2022)

An Overview on Promising Somatic Cell Sources Utilized for the Efficient Generation of Induced Pluripotent Stem Cells - Arnab Ray; Jahnavy Madhukar Joshi; Pradeep Kumar Sundaravadivelu; Khyati Raina; Nibedita Lenka; Vishwas Kaveeshwar; Rajkumar P Thummer (Stem Cell Reviews and Reports, 2021)

Temporal trends in frost occurrence and their prediction models using multivariate statistical techniques for two diverse locations of Northern India - Santanu Kumar Bal; Rajkumar Dhakar; P. Vijaya Kumar; Adita Mishra; V. P. Pramod; M. A. Sarath Chandran; V. M. Sandeep; A. V. M. Subba Rao; K. K. Gill; Rajendra Prasad (Theoretical and Applied Climatology, 2021)

Quantification of greenhouse gas emissions from managed biofuel plantations in a semi-arid landscape of Southern India - G. R. Rao; P. Sathi Reddy; M. Rajkumar (Tropical Ecology, 2021)

Emerging COVID-19 Neurological Manifestations: Present Outlook and Potential Neurological Challenges in COVID-19 Pandemic - Saikat Dewanjee; Jayalakshmi Vallamkondu; Rajkumar Singh Kalra; Nagaprasad Puvvada; Ramesh Kandimalla; P. Hemachandra Reddy (Molecular Neurobiology, 2021)

An Insight into the Role of UTF1 in Development, Stem Cells, and Cancer - Khyati Raina; Chandrima Dey; Madhuri Thool; S Sudhagar; Rajkumar P Thummer (Stem Cell Reviews and Reports, 2021)

Biomechanical Regulation of Hematopoietic Stem Cells in the Developing Embryo - Paulina D. Horton; Sandeep P. Dumbali; Krithikaa Rajkumar Bhanu; Miguel F. Diaz; Pamela L. Wenzel (Current Tissue Microenvironment Reports, 2021)
Purpose of Review The contribution of biomechanical forces to hematopoietic stem cell (HSC) development in the embryo is a relatively nascent area of research. Herein, we address the biomechanics of the endothelial-to-hematopoietic transition (EHT), impact of force on organelles, and signaling triggered by extrinsic forces within the aorta-gonad-mesonephros (AGM), the primary site of HSC emergence. Recent Findings Hemogenic endothelial cells undergo carefully orchestrated morphological adaptations during EHT. Moreover, expansion of the stem cell pool during embryogenesis requires HSC extravasation into the circulatory system and transit to the fetal liver, which is regulated by forces generated by blood flow. Findings from other cell types also suggest that forces external to the cell are sensed by the nucleus and mitochondria. Interactions between these organelles and the actin cytoskeleton dictate processes such as cell polarization, extrusion, division, survival, and differentiation. Summary Despite challenges of measuring and modeling biophysical cues in the embryonic HSC niche, the past decade has revealed critical roles for mechanotransduction in governing HSC fate decisions. Lessons learned from the study of the embryonic hematopoietic niche promise to provide critical insights that could be leveraged for improvement in HSC generation and expansion ex vivo.

An Insight into Reprogramming Barriers to iPSC Generation - Krishna Kumar Haridhasapavalan; Khyati Raina; Chandrima Dey; Poulomi Adhikari; Rajkumar P. Thummer (Stem Cell Reviews and Reports, 2020)

Evaluation of heavy metal contamination in soil using geochemical indexing approaches and chemometric techniques - H. Rajkumar; P. K. Naik; M. S. Rishi (International Journal of Environmental Science and Technology, 2019)

Effect of supplementing germinated sprouts of pulses on performance, carcass variables, immune and oxidative stress indicators in broiler chickens reared during tropical summer season - S. V. Rama Rao; B. Prakash; U. Rajkumar; M. V. L. N. Raju; T. Srilatha; E. P. K. Reddy (Tropical Animal Health and Production, 2018)

Regional forcing explains local species diversity and turnover on tropical islands - Thomas Ibanez; Gunnar Keppel; Cláudia Baider; Chris Birkinshaw; Heike Culmsee; Susan Cordell; F. B. Vincent Florens; Janet Franklin; Christian P. Giardina; Thomas W. Gillespie; Melinda Laidlaw; Creighton M. Litton; et al. (Global Ecology and Biogeography, 2018)
Aim To determine the role of regional forcing on plot‐level species diversity and composition, and to quantify the relative importance of biogeographical and climatic factors in explaining woody plant diversity and composition at the local‐, island‐ and archipelago‐scale. Location Forty‐one tropical islands of the Indo‐Pacific region from Madagascar to Hawai‘i Island. Methods We analysed the diversity and composition of tropical woody plant communities located across 113 plots, 41 islands and 19 archipelagos. We used generalized linear mixed‐effects models and generalized dissimilarity models to determine the role of regional forcing at the island and archipelago scale and to assess the relative importance of biogeographical (area and isolation of islands or archipelagos, geographical distance between plots) and climatic factors in explaining differences in local diversity and composition (species turnover). Analyses were conducted at different geographical scales (local, island and archipelago) and taxonomic levels (species, genus and family). Results Variation in local (plot‐level) diversity (as species density, the number of species per 100 woody plants) was primarily explained by island and archipelago identity. Maximum species density was positively correlated with the area of an island (or archipelago) and negatively correlated with the isolation of an archipelago. Local climatic variability was also a significant predictor of species density, but less important than regional forcing. Climate variables explained Main conclusions Regional forcing was the key driver of local diversity and composition on islands. Island area and archipelago isolation are likely driving local diversity through their effects on the pool of island species. Geographical distance between plots is the main factor explaining species turnover, while at higher taxonomic levels, climatic factors and niche conservatism are the main drivers.

Lead Modulates Calcium Entry and Beta-Adrenoceptors Signaling to Produce Myometrial Relaxation in Rats - Udayraj P. Nakade; Abhishek Sharma; Soumen Choudhury; Rajkumar Singh Yadav; Satish Kumar Garg (Biological Trace Element Research, 2017)

Identification and agro-morphological characterization of rice genotypes resistant to sheath blight - Susmita Dey; Jyothi Badri; V. Prakasam; V. P. Bhadana; K. B. Eswari; G. S. Laha; C. Priyanka; Aku Rajkumar; T. Ram (Australasian Plant Pathology, 2016)

Predicting Irrigated and Rainfed Rice Yield Under Projected Climate Change Scenarios in the Eastern Region of India - A. V. M. Subba Rao; Arun K. Shanker; V. U. M. Rao; V. Narsimha Rao; A. K. Singh; Pragyan Kumari; C. B. Singh; Praveen Kumar Verma; P. Vijaya Kumar; B. Bapuji Rao; Rajkumar Dhakar; M. A. Sarath Chandran; et al. (Environmental Modeling & Assessment, 2016)

Assessment of terminal heat tolerance ability of wheat genotypes based on physiological traits using multivariate analysis - Shivani Nagar; V. P. Singh; Ajay Arora; Rajkumar Dhakar; Shiv Ramakrishnan (Acta Physiologiae Plantarum, 2015)

Rapid Diagnosis and Simultaneous Identification of Tuberculous and Bacterial Meningitis by a Newly Developed Duplex Polymerase Chain Reaction - Khushboo J. Nagdev; Sharda P. Bhagchandani; Shradha S. Bhullar; Rajkumar C. Kapgate; Rajpal S. Kashyap; Nitin H. Chandak; Hatim F. Daginawala; Hemant J. Purohit; Girdhar M. Taori (Indian Journal of Microbiology, 2015)

Molecular diversity of Bipolaris oryzae infecting Oryza sativa in India - A. Kandan; J. Akhtar; B. Singh; D. Dixit; D. Chand; A. Roy; S. Rajkumar; P. C. Agarwal (Phytoparasitica, 2015)

Biopharmaceutical considerations and characterizations in development of colon targeted dosage forms for inflammatory bowel disease - Rajkumar Malayandi; Phani Krishna Kondamudi; P. K. Ruby; Deepika Aggarwal (Drug Delivery and Translational Research, 2014)

Preliminary studies on the characterization of clay minerals in the Sundarban mangrove core sediments, West Bengal, India - K. Rajkumar; AL. Ramanathan; P. N. Behera; S. Chidambaram (Arabian Journal of Geosciences, 2014)

Molecular mapping of genomic regions harbouring QTLs for root and yield traits in sorghum (Sorghum bicolor L. Moench) - Rajkumar; B. Fakrudin; S. P. Kavil; Y. Girma; S. S. Arun; D. Dadakhalandar; B. H. Gurusiddesh; A. M. Patil; M. Thudi; S. B. Bhairappanavar; Y. D. Narayana; P. U. Krishnaraj; et al. (Physiology and Molecular Biology of Plants, 2013)

Outcome definitions and clinical predictors influence pharmacogenetic associations between HTR3A gene polymorphisms and response to clozapine in patients with schizophrenia - A. P. Rajkumar; B. Poonkuzhali; A. Kuruvilla; A. Srivastava; M. Jacob; K. S. Jacob (Psychopharmacology, 2012)

Ione kipgenii (Orchidaceae), a new species from Manipur, India - Rajkumar Kishor; Krishna Chowlu; S. P. Vij (Kew Bulletin, 2012)

An examination of male and female odds ratios by BMI, cigarette smoking, and alcohol consumption for cancers of the oral cavity, pharynx, and larynx in pooled data from 15 case–control studies - Jay H. Lubin; Joshua Muscat; Mia M. Gaudet; Andrew F. Olshan; Maria Paula Curado; Luigino Dal Maso; Victor Wünsch-Filho; Erich M. Sturgis; Neonilia Szeszenia-Dabrowska; Xavier Castellsague; Zuo-Feng Zhang; Elaine Smith; et al. (Cancer Causes & Control, 2011)

Genetic analysis of juvenile growth and carcass traits in a full diallel mating in selected colored broiler lines - Ullengala Rajkumar; R. P. Sharma; M. K. Padhi; K. S. Rajaravindra; B. L. N. Reddy; M. Niranjan; T. K. Bhattacharya; S. Haunshi; R. N. Chatterjee (Tropical Animal Health and Production, 2011)

Polymorphism in the Prolactin Promoter and Its Association with Growth Traits in Chickens - T. K. Bhattacharya; R. N. Chatterjee; R. P. Sharma; M. Niranjan; U. Rajkumar; B. L. N. Reddy (Biochemical Genetics, 2011)

First record of three giant marine Bathynomids (Crustacea, Isopoda, Cirolanidae) from India - R. Sankar; M. Rajkumar; Jun Sun; A. Gopalakrishnan; T. M. Vasanthan; G. Ananthan; J. P. Trilles (Acta Oceanologica Sinica, 2011)

Biodiversity of brackish water amphipods (crustacean) in two estuaries, southeast coast of India - Nityananda Mondal; Mayalagu Rajkumar; Jun Sun; Sourav Kundu; P. S. Lyla; Seyed Ajmal Khan; Jean Paul Trilles (Environmental Monitoring and Assessment, 2010)

Bloom forming species of phytoplankton in two coastal waters in the Southeast coast of India - K. Thillai Rajasekar; M. Rajkumar; Jun Sun; V. Ashok Prabu; P. Perumal (Journal of Ocean University of China, 2010)

Seasonal variations of phytoplankton diversity in the Coleroon coastal waters, southeast coast of India - Rajasekar K. Thillai; M. Rajkumar; Jun Sun; Prabu V. Ashok; P. Perumal (Acta Oceanologica Sinica, 2010)

AFLP-Based Genetic Diversity Assessment of Commercially Important Tea Germplasm in India - R. K. Sharma; M. S. Negi; S. Sharma; P. Bhardwaj; R. Kumar; E. Bhattachrya; S. B. Tripathi; D. Vijayan; A. R. Baruah; S. C. Das; B. Bera; R. Rajkumar; et al. (Biochemical Genetics, 2010)

Influence of Silver Nanoparticles on 2,3-Bis(Chloromethyl)Anthracene-1,4,9,10-Tetraone - Mahalingam Umadevi; N. A. Sridevi; A. S. Sharmila; Beulah J. M. Rajkumar; M. Briget Mary; P. Vanelle; T. Terme; O. Khoumeri (Journal of Fluorescence, 2010)

Effects of selected heavy metals (Pb, Cu, Ni, and Cd) in the aquatic medium on the restoration potential and accumulation in the stem cuttings of the terrestrial plant, Talinum triangulare Linn - K. Rajkumar; S. Sivakumar; P. Senthilkumar; D. Prabha; C. V. Subbhuraam; Y. C. Song (Ecotoxicology, 2009)

Fluorescence Quenching of 1,4-Dihydroxy-2,3-Dimethyl-9,10-Anthraquinone by Silver Nanoparticles: Size Effect - M. Umadevi; P. Vanelle; T. Terme; Beulah J. M. Rajkumar; V. Ramakrishnan (Journal of Fluorescence, 2009)

High Level of Genetic Diversity Among the Selected Accessions of Tea (Camellia sinensis) from Abandoned Tea Gardens in Western Himalaya - S. Karthigeyan; S. Rajkumar; R. K. Sharma; Ashu Gulati; R. K. Sud; P. S. Ahuja (Biochemical Genetics, 2008)

Spectral Investigations of Solvatochromism and Preferential Solvation on 1,4-Dihydroxy-2,3-Dimethyl-9,10-Anthraquinone - M. Umadevi; P. Vanelle; T. Terme; Beulah J.M. Rajkumar; V. Ramakrishnan (Journal of Fluorescence, 2008)

Molecular mapping of genomic regions harboring QTLs for stalk rot resistance in sorghum - P. Srinivasa Reddy; B. Fakrudin; Rajkumar; S. M. Punnuri; S. S. Arun; M. S. Kuruvinashetti; I. K. Das; N. Seetharama (Euphytica, 2008)

Genetics of rate limiting disease reaction to Alternaria solani in Tomato - E. S. Rao; A. D. Munshi; P. Sinha; Rajkumar (Euphytica, 2008)

Correlation between Waardenburg syndrome phenotype and genotype in a population of individuals with identified PAX3 mutations - Anita L. DeStefano; L. Adrienne Cupples; Kathleen S. Arnos; J. H. Jr. Asher; Clinton T. Baldwin; Susan Blanton; Melisa L. Carey; Elias O. da Silva; T. B. Friedman; Jacquie Greenberg; Anil K. Lalwani; Aubrey Milunsky; et al. (Human Genetics, 1998)